Kinetic Study on Heavy Metal Divalent Ions Removal using Zirconium-Based Magnetic Sorbent - Lim, Soh Fong; Lee, A. Y. W.; Chua, S. N. D; Lim, B.H. (UTHM Publisher, 2020)
In this research, zirconium-based magnetic sorbent synthesised by chemical co-precipitation method is explored as a potential sorbent for removal of divalent metal ions from aqueous solution. The interaction characteristics between the ions and the sorbent were elucidated by instrumental analyses such as Fourier Transform InfraRed (FT-IR) Spectroscopy, Scanning Electron Microscopy (SEM), and Brunauer, Emmett, and Teller (BET) surface area analyser. Results show that the sorption rate was increased with an increase in contact time and initial metal ion concentration. Moreover, a two-stage kinetics behaviour was observed, and all the batch experiments achieved an equilibrium state within 4 hours. The evaluation of the adsorption behaviour of heavy metal divalent ions onto the magnetic sorbent was explained using two kinetic models, and it was mostly found to follow the postulate of the pseudo-second-order kinetic model. The validity of kinetic models applied in this study is also evaluated by using a normalised standard deviation.